Solve for y square root of y=-6

Math
y=-6
To remove the radical on the left side of the equation, square both sides of the equation.
y2=(-6)2
Simplify each side of the equation.
Tap for more steps…
Multiply the exponents in (y12)2.
Tap for more steps…
Apply the power rule and multiply exponents, (am)n=amn.
y12⋅2=(-6)2
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
y12⋅2=(-6)2
Rewrite the expression.
y1=(-6)2
y1=(-6)2
y1=(-6)2
Simplify.
y=(-6)2
Raise -6 to the power of 2.
y=36
y=36
Exclude the solutions that do not make y=-6 true.
No solution
Solve for y square root of y=-6

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top